EFEKTIVITAS METODE MELATIH MENGGUNAKAN ALAT BANTU PELAMPUNG DAN TANPA ALAT BANTU PELAMPUNG TERHADAP KECEPATAN RENANG GAYA BEBAS 5O METER - Firta suli, Risma Ananda; Sumantri, Ajis (Educative Sportive, 2021)
Abstract This study aims to determine the effectiveness of the training method using a buoy and without a buoy on the 50 meter freestyle swimming speed. This study used an experimental method with a "two group pretest-posttest design" design. The sample in this study were athletes from the RD Club of Rejang Lebong Regency, totaling 10 children. The sampling technique used purposive sampling, with the criteria (1) Subjects aged 8 to 18 years, (2) Ideal body weight, (3) Competent, (4) Minimum regional level achievement, (5) Mastering 4 styles. Analysis of the data using the t test. The research shows that: (1) there is an effect of exercise using a buoy on the speed of the 50 meter freestyle swimming, with t count 3.053 > t table 2.131 and a significance value of 0.038 < 0.05, with a difference of increase of 0.83. (2) there is an effect of exercise without using a buoy on the speed of the 50 meter freestyle swimming, with t count 2.840 > t table 2.131 and a significance value of 0.047 < 0.05, with an increase difference of 0.66. (3) the training method using a buoy is more effective than without using a buoy on the 50 meter freestyle swimming speed, with t count 0.268 < t table 1.859 and a significant value of 0.795 > 0.05, with a posttest average difference of 0 ,47. Keyword: Effectiveness, Training, Speed